Qualifying collective behavior in expanding ultracold gases as a function of particle number - Flörchinger, Stefan; Giacalone, Giuliano; Heyen, Lars H.; Tharwat, Leena (Physical review, 2022)
Collective phenomena in quantum many-body systems are often described in terms of hydrodynamics, an appropriate framework when the involved particle numbers are effectively macroscopic. We propose to use experiments on expanding clouds of few and many interacting cold atoms to investigate the emergence of hydrodynamics as a function of particle number. We consider gases confined in two-dimensional elliptically deformed traps, and we employ the manifestation of elliptic flow as an indicator of collective behavior. We quantify the response of the gas to the deformation of the trapping potential, and show how such information can be used to establish how many atoms are needed for the system to develop a degree of collectivity comparable to that expected in the hydrodynamic limit. This method permits one, in particular, to exploit observations made in expanding atomic gases to shed light on the apparent hydrodynamic behavior of mesoscopic systems of quarks and gluons formed in the scattering of light ions in high-energy collider experiments.
Gesehen am 20.06.2022